Analysis of factors influencing the incidence of adverse drug reaction (ADR) in the use of first-line anti-tuberculosis drugs in pulmonary tuberculosis patients at Randegansari Husada Gresik Hospital - Fardhiyanti, Fardhiyanti; Sutrisna, Em (Science Midwifery, 2024)
The success of TB treatment is one of the levels of patient compliance in undergoing treatment, TB patients who are not compliant in undergoing treatment are due to long-term drug use, possible side effects, and lack of awareness of their disease. Dangerous and unexpected responses from a drug that occur at a common dose are called Adverse Drug Reactions (ADR). This study aims to determine the factors that influence the incidence of ADR in the use of pulmonary anti-tuberculosis drugs at Randegansari Husada Hospital. This study uses an observational study type with a cross-sectional design through retrospective data through medical records of category I pulmonary TB patients using the first-line OAT regimen at Randegansari Husada Hospital. Descriptive data analysis to determine the incidence of ADR and Chi Square tests were carried out. Correlation between factors using logistic analysis regression method. The results showed that the highest level of ADR severity was reddish urine, more than 50% of patients experienced ADR of more than 3. The risk factors found in this study were age, gender, occupation, OAT drugs used, history of comorbidities, and receiving additional drugs. Therapy for handling the side effects of tuberculosis has been carried out according to the symptoms experienced.